Comparative effectiveness of multiple androgen receptor signaling inhibitor medicines with androgen deprivation therapy for metastatic hormone-sensitive prostate cancer: a study in the real world - Lu, Yutong; Jiang, Jingqi; Yang, Gaoyang; Ding, Hui; Zheng, Qihui; Ji, Luhua; Wang, Yuhan; Dong, Zhilong; Zhai, Zhenxing; Tian, Junqiang; Zhang, Yunxing; Wang, Juan; et al. (Frontiers in Oncology, 2024)
We retrospectively analyzed 82 patients diagnosed with mHSPC. We evaluated PSA progression-free survival (PSA-PFS), imaging progression-free survival (r PFS), castration resistance progression-free survival (CRPC-PFS), and overall survival (OS) using Kaplan-Meier survival analyses. Additionally, we explored relevant factors affecting prognosis through univariate and multivariate Cox risk-proportionality models. PSA response rates at 3, 6, and 12 months, nadir PSA levels ( nPSA), and time to nadir (TTN) in different medication subgroups after treatment were documented, and we used one-way ANOVA to determine the effect of these measures on patient prognosis. Result: In comparison with bicalutamide, both enzalutamide and apalutamide have shown significant advantages in delaying disease progression among mHSPC patients. Specifically, enzalutamide has been found to significantly prolong PSA-PFS (HR 2.244; 95% CI 1.366-3.685, p=0.001), rPFS (HR 2.539; 95% CI 1.181-5.461; p= 0.007), CRPC-PFS (HR 2.131; 95% CI 1.295-3.506; p= 0.003), and OS (HR 2.06; 95% CI 1.183-3.585; P=0.005). Similarly, apalutamide has significantly extended PSA-PFS (HR 5.071; 95% CI 1.711-15.032; P= 0.003) and CRPC-PFS (HR 6.724; 95% CI 1.976-22.878; P=0.002) among patients. On the other hand, the use of abiraterone in combination with ADT did not demonstrate a significant advantage in delaying diseases progression when compared with the other three agents in mHSPC patients. There were no significant differences in overall adverse event rates among the four pharmaceuticals in terms of safety. Additionally, the observation of PSA kinetics revealed that enzalutamide, apalutamide, and abiraterone acetate had a significant advantage in achieving deep PSA response (PSA ≤ 0.2 ng/ml) compared with bicalutamide (p=0.007 at 12 months). Enzalutamide and apalutamide exhibited preeminence efficacy, with no substantial difference observed between the two medications. Abiraterone, enzalutamide, and apalutamide were found to significantly reduce and stabilize PSA levels in mHSPC patients more quickly and thoroughly than bicalutamide. Furthermore, enzalutamide and apalutamide were found to significantly prolong survival and delay disease progression in mHSPC patients compared with bicalutamide. It should be noted that abiraterone did not demonstrate a significant advantage in delaying disease compared with enzalutamide and apalutamide. After conducting drug toxicity analyses, it was determined that there were no significant differences among the four drugs.